2009
DOI: 10.1086/644621
|View full text |Cite
|
Sign up to set email alerts
|

Hemolytic Uremic Syndrome and Death in Persons withEscherichia coliO157:H7 Infection, Foodborne Diseases Active Surveillance Network Sites, 2000–2006

Abstract: Young children and females had an increased risk of HUS after STEC O157 infection. With or without HUS, elderly persons had the highest proportion of deaths associated with STEC O157 infection. These data support recommendations for aggressive supportive care of young children and the elderly early during illness due to STEC O157.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
146
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(159 citation statements)
references
References 19 publications
7
146
2
2
Order By: Relevance
“…Multiple studies have demonstrated sensitivity of Ͼ97% for nucleic acid amplification tests (NAATs) designed to detect STEC (stx 1 and stx 2 ) and E. coli serotype O:157 (rfbE) directly from preserved stool specimens in as little as 1 to 4 h (7,(12)(13)(14)(15). Some of these NAATs are specific for STEC, while others are highly multiplexed to enable detection of numerous bacterial, viral, and toxin targets associated with AGE.…”
mentioning
confidence: 99%
“…Multiple studies have demonstrated sensitivity of Ͼ97% for nucleic acid amplification tests (NAATs) designed to detect STEC (stx 1 and stx 2 ) and E. coli serotype O:157 (rfbE) directly from preserved stool specimens in as little as 1 to 4 h (7,(12)(13)(14)(15). Some of these NAATs are specific for STEC, while others are highly multiplexed to enable detection of numerous bacterial, viral, and toxin targets associated with AGE.…”
mentioning
confidence: 99%
“…Shiga toxin-producing Escherichia coli STEC bacteria, including the O157 serogroup, are welldescribed human pathogens associated with bloody diarrhea, hemolytic-uremic syndrome HUS , and death Gould et al, 2009 . Illnesses are often attributed to the consumption of contaminated food or water; however, transmission by animal contact may also be important Hale et al, 2012, Rangel et al, 2005 .…”
mentioning
confidence: 99%
“…Among patients diagnosed with STEC, 6 % subsequently develop hemolytic uremic syndrome. 1 Microbiologic detection of STEC is highly dependent on obtaining stool cultures within 6 days of symptom onset, and the presence of fecal leukocytes indicates a higher yield sample. 2 The gold standard for diagnosis is stool culture on sorbitol MacConkey agar, followed by latex agglutination.…”
mentioning
confidence: 99%